Fertilización del híbrido de maíz, ICA H302, con fósforo y zinc en un suelo del oriente de Cundinamarca (1978)
In order to observe the response of corn H-302, to P and Zn applications in a soil east Cundinamarca, municipio de Ubaque, vereda Centro, greenhouse and field trials were performed, using a central composit design with 5 levels of each one of these two elements. Dry matter yields of 6 weeks corn plants showed that P levels for maximum production varies from 85 to 100 kg of P2 05 /Ha. P level for maximum yields increases with the increase of Zn SO4 applications. Phosphorus - Zn interaction showed negative effect on grain production. Independently, P and Zn effects were positive. Maximum yields were not obtained with the P and Zn levels used, but is probable that in soils of this nature, high in available P s not economical to apply this element. Perhaps it is more practical to use only Zn SO4 to increase corn yields in these soils. Negative effects were found in P and Zn concentrations in corn plants when Zn and P were added to the soil, respectively. The amounts of available P and Zn in the soil were not affected by applications of these two elements (Zn in the case of P and viceversa). The results can possibly support the idea that P - Zn antagonistic effect is more of a physiological type within the plant than of a chemical one in the soil.